2019
DOI: 10.1002/ps.5631
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal and cercaricidal activities of curcumin on Biomphalaria glabrata and Schistosoma mansoni cercariae

Abstract: BACKGROUND Schistosomiasis control in endemic areas depends on several factors, including chemotherapy, snail control and adequate sanitation. In this context, the employment of compounds isolated from plants is an important issue regarding infection and snail control. The aim of this study was therefore to evaluate the effects of curcumin (CUR), a compound isolated from Curcuma longa, against snails and embryos of Biomphalaria glabrata, which is the most important intermediate host of schistosomiasis in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…sylvestris extract eliminated 100 % of the worms after incubation for 72 and 48 h, respectively. On the other hand, at 12.5, 25, and 50 μg/mL ( Table 3), the extract reduced parasite viability moderately; that is, they displayed moderate schistosomidal activity [25,26] . Nevertheless, the var.…”
Section: Resultsmentioning
confidence: 97%
“…sylvestris extract eliminated 100 % of the worms after incubation for 72 and 48 h, respectively. On the other hand, at 12.5, 25, and 50 μg/mL ( Table 3), the extract reduced parasite viability moderately; that is, they displayed moderate schistosomidal activity [25,26] . Nevertheless, the var.…”
Section: Resultsmentioning
confidence: 97%
“…Jia et al (2019) documented that the pentacyclic triterpenoid saponin derived from Camellia oleifera has molluscicidal activity against Oncomelania hupensis, Biomphalaria alexandrina and Bulinus truncatus. Matos et al (2020) proved that the curcumin extract has molluscicidal activity against Biomphalaria glabrata and stated that the embryo development, egg hatching and fecundity rate of adult snails were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, experiments have been proven toxic to non-target organisms such as fish (Lemma, 1970). Matos et al (2020) found a fatal effect of curcumin on snails (Biomphalaria glabrata) and cercariae in Schistosoma mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…In a context of schistosomiasis elimination goal, the characterization of biological activities from plant-derived compounds mainly focuses on molluscicidal toxicity to break the parasite transmission cycle. However, some promising candidates present a dual activity by causing either the death of infective larvae [ 16 , 17 , 65 – 67 ] or developmental abnormalities leading to a low pathogenicity [ 68 ]. Mortality values after being exposed only for 24 h at 0.5 ppm were around 75% and 95% for miracidia and cercarciae, respectively, and close to 100% for both after 4 h exposure.…”
Section: Discussionmentioning
confidence: 99%